Regulation of TAK1/TAB1-mediated IL-1β signaling by cytoplasmic PPARβ/δ. - Josefine Stockert (Public Library of Science (PLoS), 2013)
The peroxisome proliferator-activated receptor subtypes PPARα, PPARβ/δ, PPARγ are members of the steroid hormone receptor superfamily with well-established functions in transcriptional regulation. Here, we describe an unexpected cytoplasmic function of PPARβ/δ. Silencing of PPARβ/δ expression interferes with the expression of a large subset of interleukin-1β (IL-1β)-induced target genes in HeLa cells, which is preceded by an inhibition of the IL-1β-induced phosphorylation of TAK1 and its downstream effectors, including the NFκBα inhibitor IκBα (NFKBIA) and the NFκBα subunit p65 (RELA). PPARβ/δ enhances the interaction between TAK1 and the small heat-shock protein HSP27, a known positive modulator of TAK1-mediated IL-1β signaling. Consistent with these findings, PPARβ/δ physically interacts with both the endogenous cytoplasmic TAK1/TAB1 complex and HSP27, and PPARβ/δ overexpression increases the TAK1-induced transcriptional activity of NFκB. These observations suggest that PPARβ/δ plays a role in the assembly of a cytoplasmic multi-protein complex containing TAK1, TAB1, HSP27 and PPARβ/δ, and thereby participates in the NFκB response to IL-1β.